2021
DOI: 10.3390/foods10020443
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Terroir on the Flavour of Single Malt Whisk(e)y New Make Spirit

Abstract: The impact of barley variety and its geographical growth location (environment) on the flavour of new make spirit was investigated to determine if “terroir” can be applied in the production of single malt whisk(e)y. New make spirits were produced at laboratory scale under controlled conditions from two different barley varieties (Olympus and Laureate) grown at two distinct environments (Athy, Co Kildare and Bunclody, Co Wexford) in Ireland over two consecutive seasons (2017 and 2018). The spirit samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Kyraleou et al investigated the effect of terroir on flavor components in new-make malt whisky [ 74 ]. They compared new-make spirits differing by two varieties of barley, two growing environments, and two seasons, showing that environments and seasons had a greater impact on flavor than variety alone.…”
Section: Sensory Evaluation and Its Contribution To Qualitymentioning
confidence: 99%
“…Kyraleou et al investigated the effect of terroir on flavor components in new-make malt whisky [ 74 ]. They compared new-make spirits differing by two varieties of barley, two growing environments, and two seasons, showing that environments and seasons had a greater impact on flavor than variety alone.…”
Section: Sensory Evaluation and Its Contribution To Qualitymentioning
confidence: 99%
“…In this sense, CDC Copeland barley, a two-rowed malting barley, produces neutral flavors and pale colored beers. It has also been reported that, depending on the “terroir” where barley is grown, beers with different flavors can also be obtained [ 38 ].…”
Section: Barley Malt and Maltingmentioning
confidence: 99%
“…There are discussions in academia about the concept of terroir containing other factors. Terroir is a traditional concept widely used to describe the particularities of GI products; it is widely used in the wine market, although it can be applied to all agri-food products [61][62][63]. It regards the relationship between the product's quality or taste and its geographic origin [64].…”
Section: Agri-food Systemsmentioning
confidence: 99%